Balloon Mitral Valvuloplaty (BMV): An early experience in Chitwan Medical College - Regmi, S R; Dhital, B M; Sharma, B; Regmi, S (Journal of Chitwan Medical College, 2017)
Balloon Mitral Valvotomy (BMV) is one the preferred modality of treatment for Rheumatic mitral stenosis. This is usually performed with onsite surgical backup to tackle the complications like cardiac tamponade needing surgical drainage and severe mitral regurgitation which requires emergency Mitral Valve Replacement. Our aim is to evaluate the pre and post procedural outcomes of the BMV, without onsite surgical backup. Total patients were 88 who underwent BMV in Chitwan Medical College, from Feb 2014 to Jan. 2016. All symptomatic patients (NYHA class II- IV) with their mitral valve area (MVA ) <1.5cm2 were enrolled. Detail clinical evaluation and Echocardiography was done before and after the procedure. The procedure was performed under local anesthesia, using the step-wise Inoue balloon dilation with the ante grade transvenous approach. The successful procedure was 87 (98.8 %). The mean age was 38+13 yrs, mean pre BMV MVA= 0.85+0.18 cm2, mean Post BMV MVA =1.76+0.23 cm2, by plannimetry. Pre BMV mean left atrium pressure=23.10+6.79 mmHg and post BMV mean left atrium pressure=12.48+4.86mmHg.Minor complication like puncture site hematoma in 3 (3.44%) patients, vasovagal attack in 5 (5.74%) patients after intra atrial septal puncture, Ventricular arrhythmia in 3(3.44%) patients and supraventricular arrhythmia in 8 (9.19%) patients. Severe mitral regurgitation occurred in 4 (4.59%) patients and managed medically. Cardiac tamponade developed in 1(1.2%) patient, pericardiocentesis done. Balloon Mitral Valvotomy is safe and effective procedure for patient with severe and symptomatic patient with Rheumatic MS. It can be formed without onsite surgical backup with experience hand.